Explanation on Breast Milk Management for Working Mothers at Waluya Malang Original Hospital - Susmini (Journal of Community Service for Health, 2022)
Breast milk is very important for the fulfillment of infant nutrition from the beginning of birth to the first 6 months. Until now, the conten of breast milk has no been superior in meeting nutritional needs to the formation of the immune system in body. Several factors cause breastfeeding not to be carried out properly due to busy working mothers. Management of the provision of nutrients that are needed to meet the needs of infants. In several studies, this knowledge in breastfeeding management is in the sufficient category. Based on this description, the researcher wants to provide counseling about the management of breastfeeding for working mothers at the Panti Waluya Hospital in Malang, which will be held on May 11 2021 at the Panti Waluya Hospital in Malang. Strategy extension activities are carried out by delivering material and discussing the management of breastfeeding for working mothers. The implementation was carried out for 2 hours with 44 participants from counseling, before sending the material, participants are encouraged to fill out the questionnaire that has been distributetd to fine out correct management of breastfeeding. Then after delivering the material, hold a question and answer session to find out the mader’s anderstanding and the implementation of breastfeeding management with the thory put forword. The method used is discussion (question and answer ), the material contains about how to manage lactation. The results obtained were most of 27 (63,3%) had less knowledge about breastfeeding management, and most 17 (36,7%) counseling participants understood about breastfeeding management and implemented it. Another factor that causes breastfeeding management is not implemented properly so that there is limited time for management and there are no breastfeeding facilities available for working mothers.